Isolation and Functional Characterization of a Green-Tissue Promoter in Japonica Rice (Oryza sativa subsp. Japonica) - Mi Lin; Jingwan Yan; Muhammad Moaaz Ali; Shaojuan Wang; Shengnan Tian; Faxing Chen; Zhimin Lin (Biology, 2022)
Plant promoters play a vital role in the initiation and regulation of gene transcription. In this study, a rice protein/gene of unknown expression, named Os8GSX7, was gained from a rice T-DNA capture line. The semi-quantitative RT-PCR analysis showed that the gene was only expressed in root, glume, and flower, but not in stem, leaf, embryo, and endosperm of japonica rice. The GUS activity analysis of the GSX7R promoter showed that it was a reverse green tissue expression promoter, except in endosperm. The forward promoter of GSX7 cannot normally drive the expression of the foreign GUS gene, while the reverse promoter of GSX7 is a green tissue-specific expression promoter, which can drive the expression of the foreign GUS gene. The region from −2097 to −1543 bp was the key region for controlling the green tissue-specific expression. The regulatory sequences with different lengths from the 2097 bp reverse sequence from the upstream region of the Os8GSX7 were fused with the GUS reporter gene and stably expressed in rice. Furthermore, transgenic rice plants carrying Cry1Ab encoding Bacillus thuringiensis endotoxin, regulated by GSX7R, were resistant to yellow stem borer. The analysis suggested that 10 light responsive elements of tissue-specific expression were found, including ACE, Box4, CAT-box, G-Box, G-box, GATA motif, GC motif, I-box, Sp1, and chs-unit1 M1. In addition, the results of 5′ and 3′ deletions further speculated that ACE and I-box may be the key elements for determining the green tissue-specific expression of GSX7R promoter.